Detectability of Liver Steatosis and Fibrosis with Transient Elastography and Controlled Attenuation Parameter in Residents of St. Petersburg - V. P. Kovyazina; K. L. Raikhelson; M. K. Prashnova; E. V. Pazenko; L. K. Palgova; E. A. Kondrashina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2021)
Aim. Estimation of the liver steatosis and fibrosis incidence with transient elastography and the controlled attenuation parameter in residents of St. Petersburg.Materials and methods. A prospective open single-centre population study included history, anthropometric and laboratory data on 318 outpatients aged 24—89 years (mean age 52.6 ± 14.6 years). The degrees of steatosis (assessed with the controlled attenuation parameter as ultrasound amplitude dropdown quantification in liver) and fibrosis were determined with a Fibroscan 502 Touch unit (Echosens, France).Results. Hepatic steatosis of predominantly high degree was revealed in 44.7%, combined fibrosis and steatosis — in 28%; isolated fibrosis of various stage — in 2.5%, no structural changes — in 24.8% individuals. The growth of body mass index and waist circumference significantly correlated in women with pronounced liver changes. Serum transaminase activity increased with more severe liver changes, being statistically significant for aspartic transaminase only.Conclusion. A high incidence of primary liver steatosis and fibrosis in residents of St. Petersburg warrants improved diagnostic algorithms and routine preventive measures. Transient elastography with the controlled attenuation parameter estimation provides a convenient non-invasive screening for hepatic fibrosis and steatosis.